Mortality Trends In Pre COVID And Pandemic Era In A Tertiary Care Setting - Hareema Saeed Khan; Savida Ilyas Dar; Tayyaba Faisal; Faridullah Shah; Rabbia Aslam; Maheen Asim (Journal of Rawalpindi Medical College)
Objective: The coronavirus pandemic has emphasized stay-at-home and social distancing policies. Since the beginning of the outbreak of COVID-19, there has been a declining trend of hospital mortality indicating that the pandemic might keep patients from seeking emergency care in a hospital setting. This study was carried out to determine the mortality trends pre-COVID and pandemic periods in a tertiary care hospital.